Integrated management of Helicoverpa armigera on gram (Cicer arietinum) - SANAP, M M; PAWAR, V M (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1993-96 for controlling gram pod borer (Helicoverpa armigera Hubner.) infesting gram (Cicer arietinum L.). Integrated pest management treatment comprising endosulfan 0.07%, neem-seedkernel extract 5% and nuclear polyhedrosis virus @ 250 larval equivalents/ha were evaluated. The field trial conducted during winter 1993-96 revealed that 3 spray application starting from initiation of flowering and subsequent 2 sprays at fortnightly intervals with tirst 2 sprays either with nuclear polyhedrosis virus @250 larval equivalent/ha or neem-seedkernal extract 5% followed by third spray with endosulfan 0.07% were most effective in controlling the gram pod borer and gave 26.94 and 27.29% increase in yield.